A study of autophagy in hemocytes of the Pacific oyster, Crassostrea gigas. Issue 10 (3rd October 2019) - Picot, Sandy; Morga, Benjamin; Faury, Nicole; Chollet, Bruno; Dégremont, Lionel; Travers, Marie-Agnès; Renault, Tristan; Arzul, Isabelle
ABSTRACT: Macroautophagy is a mechanism that is involved in various cellular processes, including cellular homeostasis and innate immunity. This pathway has been described in organisms ranging in complexity from yeasts to mammals, and recent results indicate that it occurs in the mantle of the Pacific oyster, Crassostrea gigas . However, the autophagy pathway has never been explored in the hemocytes of C. gigas, which are the main effectors of its immune system and thus play a key role in the defence of the Pacific oyster against pathogens. To investigate autophagy in oyster hemocytes, tools currently used to monitor this mechanism in mammals, including flow cytometry, fluorescent microscopy and transmission electron microscopy, were adapted and applied to the hemocytes of the Pacific oyster. Oysters were exposed for 24 and 48 h to either an autophagy inducer (carbamazepine, which increases the production of autophagosomes) or an autophagy inhibitor (ammonium chloride, which prevents the degradation of autophagosomes). Autophagy was monitored in fresh hemocytes withdrawn from the adductor muscles of oysters using a combination of the three aforementioned methods. We successfully labelled autophagosomes and observed them by flow cytometry and fluorescence microscopy, and then used electron microscopy to observe ultrastructural modifications related to autophagy, including the presence of double-membrane-bound vacuoles. Our results demonstrated that autophagy occurs in hemocytes of C. gigas and can be modulated by molecules known to modulate autophagy in other organisms. This study describes an integrated approach that can be applied to investigate autophagy in marine bivalves at the cellular level. Abbreviations: MAP1LC3: microtubule associated protein 1 light chain 3; MCA: multiple correspondence analysis; NH4 Cl: ammonium chloride; PI: propidium iodide; TEM: transmission electron microscopy